Academic Genre Instruction and Its Influence on University Writing Proficiency - Benny Krisbiantoro; Muhammad Soali (JELITA, 2024)
The ongoing debate in language education revolves around the effectiveness of pedagogical approaches in teaching writing skills, particularly the merits of Genre-Based Pedagogy versus Isolated Skill-Focused Conventional Methods, which focus on practicing individual writing skills separately. This study investigated the impact of Genre-Based Pedagogy on 16 purposively selected fourth-semester students from the English Education Department at Harapan Bangsa University. Using an experimental design, participants were divided into experimental (8 students from class A) and control (8 students from class B) groups, with pre-test and post-test assessments over eight weeks. Results showed a significant improvement in the experimental group's writing skills, with a mean post-test score of 78.75 compared to 62.25 in the control group (t = 8.12). These findings suggest that Genre-Based Pedagogy, emphasizing contextualized learning and immersion in diverse text genres, significantly enhances writing proficiency compared to conventional methods, enabling students to effectively integrate grammar, vocabulary, content development, and organizational skills tailored to specific genres.